A Major New Court Decision: Are Blurred Boundaries Worth the Price on the Eligibility Side?. Issue 1 (2nd January 2017) - Zirkel, Perry A.
ABSTRACT: Legally, the ultimate criterion for eligibility under the Individuals with Disabilities Education Act (IDEA) is whether the child needs special education. A new decision by the Ninth Circuit Court of Appeals suggests that providing various interventions and accommodations in general education might mean that a child who meets the criteria for any IDEA classification and receives such services is eligible for an individualized education program. The scope of this new decision and the relationship between special and general education are subject to several questions. However, using various individualized approaches in general education, including response to intervention, may be worth the limited risk of a judicially reversed eligibility determination.